The effect of heat stress towards growth performance and crop productivity of paddy (Oryza sativa L.) – review / Nurul Anira Zuria Mohd Zakaria - Mohd Zakaria, Nurul Anira Zuria (Faculty of Plantation and Agrotechnology, 2016)
Paddy (Oryza sativa L.) is one of the global important cereals which functional as primary source of human food that are supplied for more than 3 billion human in the world. By growing population of human in the world, the demand of rice would be higher and there are already challenges to achieve the high demand such as the increasing of temperature. According to Krishnan et. al, (2011), at the end of twenty first century, the increasing of air surface temperature were probably about 104-5.8 "C, and this will become a big problem in fulfill the food security by the reduction of yield during the heat stress. Increasing of temperature may affect the growth and development of rice during sensitive stages and the consequences, it will reduce the rice productivity. The effect that might happen is reduction of the grain weight and grain quality. The crop yield would decrease about 7-8% in rice for each increasing l°e in daytime maximum/night time minimum in temperature from 28/21 to 34/27°e (Baker et al. 1992). Plant will response towards the heat stress in difference developmental stages and the most sensitive is reproductive stage.